2006
DOI: 10.1088/0953-4075/39/4/006
|View full text |Cite
|
Sign up to set email alerts
|

The dissociative recombination of fluorocarbon ions III: CF+2and CF+3

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden SPONSORING/MONITORING AGENCY NAME(S) AND ADDRESS(ES) 10. SPONSORIMONITOR'S A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…The value was used in several studies [4,17] until 2004, when the value of 2.8 ± 0.8 × 10 −7 cm 3 s −1 at 300 K, about a factor of three smaller than the above one, was measured using a flowing afterglow Langmuir probe-mass spectrometer apparatus [18]. A similar value of 2.6 × 10 −7 cm 3 s −1 at 300 K was obtained from the DR cross section measured in the ASTRID storage ring experiment two years later [11]. A further measurement of the rate coefficient was performed by another FALP experiment in 2013 [19], which produced the value of 3.1 ± 0.9 × 10 −7 cm 3 s −1 .…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The value was used in several studies [4,17] until 2004, when the value of 2.8 ± 0.8 × 10 −7 cm 3 s −1 at 300 K, about a factor of three smaller than the above one, was measured using a flowing afterglow Langmuir probe-mass spectrometer apparatus [18]. A similar value of 2.6 × 10 −7 cm 3 s −1 at 300 K was obtained from the DR cross section measured in the ASTRID storage ring experiment two years later [11]. A further measurement of the rate coefficient was performed by another FALP experiment in 2013 [19], which produced the value of 3.1 ± 0.9 × 10 −7 cm 3 s −1 .…”
Section: Introductionsupporting
confidence: 56%
“…The branching ratio for the two channels was determined in the ASTRID storage ring experiment to be 80 ± 10% and 20 ± 10%, respectively [11]. CF and CF 2 radicals in the plasma contribute to the polymerization of fluorocarbon on the substrate surface, which impacts significantly the etching rate and selectivity [12].…”
Section: Introductionmentioning
confidence: 99%
“…At pressures of 10 -6 Torr, Eyler et al 28 observed that CF2 + ions were only present in small traces that reacted swiftly with the CF4 neutral species to form CF3 + ions and so they were essentially absent from the ICR-MS work within 5 ms. At pressures of 0.1 Torr and higher Ehlerding et al 29 produced CF2 + ions in substantial quantities at 1 Torr in quantities sufficient to provide feed stock for CF2H + generation. At 50 Td the CF2 + ions can react with H2O by proton extraction to form CF2H + .…”
Section: Resultsmentioning
confidence: 99%
“…29 produced CF 2 + ions in substantial quantities and at 1 Torr in quantities sufficient to provide feed stock for CF 2 H + generation. At 50 Td the CF 2 + ions can react with H 2 O…”
mentioning
confidence: 99%
“…Cross sections and branching ratios for electron-impact dissociative recombination by + CF 3 and + CF 2 were measured by Ehlerding et al [134] through ASTRID and CRYRING storage rings. Flowing Afterglow-Langmuir Probe (FALP) measurements carried out by Fournier et al [135] agreed with the previous results for dissociative recombination of + CF 3 [134,136]. Electron-impact dissociative recombination by CF + was studied by Novotny et al [137][138][139].…”
Section: Electron-ion Reactionsmentioning
confidence: 99%